Maternal and fetal C-reactive protein genotype and first trimester CRP concentrations in maternal plasma - Hackney, David N.; Dunigan, James T.; Simhan, Hyagriv N. (Journal of reproductive immunology, 2008)
Maternal plasma CRP concentrations in pregnancy are increased over pre-pregnancy values and high concentrations have been associated with adverse obstetrical outcomes. The objective of this study was to explore the relationship between maternal and fetal variation in C-reactive protein (CRP) genotype and maternal plasma CRP concentrations in the first trimester in low risk patients. DNA was extracted from maternal and cord blood of subjects in a prospective observational cohort. Single-nucleotide polymorphism (SNP) selection was made using a linkage disequilibrium bin approach. CRP concentrations were measured in first trimester maternal plasma using an enzyme-linked immunosorbent assay (ELISA) kit. Kruskal–Wallis rank testing was used to analyze genetic and clinical determinants of CRP concentrations. Genotype results were available in 190 mother–baby pairs. There was no significant difference in CRP concentration among maternal or fetal CRP genotypes. Thus, first trimester concentrations of maternal plasma CRP in low risk subjects do not appear to be significantly associated with CRP genotype. Instead, differences in clinical factors probably have more influence on baseline maternal CRP concentrations.